Impact of organic-inorganic nutrients combination on the occurrence of rice sheath mite, Steneotarsonemus spinki Smiley (Acari:Tarsonemidae) in West Bengal - Krishna Karmakar; Pranab Debnath (Persian Journal of Acarology)
Rice sheath mite, Steneotarsonemus spinki Smiley (Acari: Tarsonemidae), was observed to pose a serious threat to the rice cultivation under Bengal Basin of West Bengal, India during wet season. The mite appeared during tillering to panicle emergence with a maximum population encountered during early ripening stage of the crop causing characteristic brownish specks on the leaf sheath and on the grains resulting poor yield particularly in case of susceptible rice cultivars, IET-4786, IR-36, IET-4094 and many others high yielding varieties. Acaricides was found to be inadequate in suppressing the mite population. The result of the experiment reveals that the mite population significantly varied among different treatments with a maximum mite population colonized (929.67 mite/ leaf sheath) in chemical fertilized plots and a minimum recorded (108.33 mite/leaf sheath) in leaf manure of Glyricidia maculata  (Kunth) Walp treated plots. However, maximum seed yield (fresh rough grain) was obtained from combined application of mustard cake, Glyricidia leaf manure and chemical fertilizers. (9.16 t/ha) which was at par with that of chemical fertilizer treated plots and the minimum yield was recorded from control plots (6.18 t/ha).